ChemInform Abstract: Metal Free Visible Light Driven Oxidation of Alcohols to Carbonyl Derivatives Using 3, 6‐Di(pyridin‐2‐yl)‐1, 2, 4, 5‐tetrazine (Pytz) as Catalyst. Issue 8 (February 2016) - Samanta, Suvendu; Biswas, Papu
Abstract: The highly efficient metal free oxidation is suitable for a wide range of primary and secondary alcohols with various functional groups and proceeds under visible light irradiation using molecular oxygen or tert‐butylnitrite as co‐oxidant.